Seasonal and spatial variation in the reproductive biology of the dwarf seahorse Hippocampus zosterae. Issue 2 (30th April 2019) - Rose, Emily; Simmonds, Mackenzie; Hayashida‐Boyles, Alana L.; Masonjones, Heather D.
Abstract: Factors associated with the reproductive ecology of the dwarf seahorse Hippocampus zosterae were investigated. Fish from a Tampa Bay (FL, USA) seagrass ecosystem were collected, photographed and returned to the wild, with photos analysed to determine patterns of body size, density, sex ratio and reproductive state across site and season to understand the population dynamics of H. zosterae over time. Animal density did not vary significantly with site and season, indicating there is little evidence of seasonal migration in this species. Densities reported in this study were higher than the mean density for all seahorse species Hippocampus spp. There was no sexual dimorphism in body length and both sexes reached sexual maturity at the same size. The ratio of gravid to non‐gravid males was found to shift by season but not by site, with breeding detected year‐round in this population compared with populations further north in their range. Peak breeding (70% gravid males) was observed in the late summer–autumn (August–October) in the site furthest from shore. The largest fish for both sexes were recorded during the summer and autumn months in the mid‐shore, deepest site. Sex ratio shifted by site with even sex ratios near the shore but significantly female‐biased sex ratios detected at sites near open water. Lastly, an increase in marking dates with decreased time intervals between collections did not yield a higher recapture rate, compared with sampling in 2010. However, the Tampa Bay population of dwarf seahorses demonstrated stable densities across 3 years with year‐round breeding, indicating that it is a robust population worthy of long‐term monitoring for conservation efforts.